SEM and systematic studies of Steinernema abbasi Elawad et al., 1997, and S. riobrave Cabanillas et al., 1994 (Rhabditida: Steinernematidae) - Nguyen, Khuong B.; Adams, Byron J. (Zootaxa, 2003)
SEM studies of the two nematodes Steinernema abbasi and S. riobrave revealed that they have two horn-like structures on the labial region similar to those of S. bicornutum, S. ceratophorum, S. pakistanense, and S. thermophilium. The structures were not mentioned in the original descriptions. In addition , S. riobrave has the twelfth pair of genital papillae at the edge of the cloaca. The papillae at this position were reported only in S. scapterisci. The formula of the lateral field pattern of S. abbasi is 2, 6, 8, 7, 6, 2, and that of S. riobrave is 2, 7, 8, 6, 2. Phylogenetic trees from sequences of D2/D3, and ITS regions of Steinernema species show that the four species S. abbasi, S. bicornutum, S. ceratophorum, and S. riobrave comprise a monophyletic group. These relationships support the present morphological studies.